2016
DOI: 10.1016/j.neuron.2016.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Neurotechnology and Society: Strengthening Responsible Innovation in Brain Science

Abstract: Technological advances have the potential to dramatically increase our understanding of the human brain, treat and cure injury and disease, and enhance our general well-being. While advances in neuroscience hold great promise, they also raise profound ethical, legal, and social questions. In this vein, the Organization for Economic Co-operation and Development (OECD) convened an international workshop in September 2016 to explore responsible research and innovation in brain science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…The scope of neuro-advancements ranges from medical/therapeutic, military, education, human enhancement to recreational, including the use of mainstream neuro-assistive technologies by disabled people and mainstream society [10,11,[20][21][22][23][24]. Some products and enabled procedures are transcranial direct stimulation techniques, neurosurgery, deep brain stimulation, artificial hippocampus, artificial brain, prosthetic memory device, cognitive enhancement and nootropic drugs [22,[25][26][27][28].…”
Section: Scope Of Neuro-advancementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The scope of neuro-advancements ranges from medical/therapeutic, military, education, human enhancement to recreational, including the use of mainstream neuro-assistive technologies by disabled people and mainstream society [10,11,[20][21][22][23][24]. Some products and enabled procedures are transcranial direct stimulation techniques, neurosurgery, deep brain stimulation, artificial hippocampus, artificial brain, prosthetic memory device, cognitive enhancement and nootropic drugs [22,[25][26][27][28].…”
Section: Scope Of Neuro-advancementsmentioning
confidence: 99%
“…Some products and enabled procedures are transcranial direct stimulation techniques, neurosurgery, deep brain stimulation, artificial hippocampus, artificial brain, prosthetic memory device, cognitive enhancement and nootropic drugs [22,[25][26][27][28]. As the innovation of neuro-advancements continues to grow, it has begun to converge outside the clinical and research settings, blurring the line between therapeutic and non-therapeutic use [10,11,29,30]. With the rise of "dual use" technologies of " .…”
Section: Scope Of Neuro-advancementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, patients demand a major involvement in the developing process of the technology programmed for their own use and rehabilitation, and also a major attention to the specific needs of their particular disease, given that different classes of patients have different requirements (Sullivan et al, 2017). It is all too common for a preclinical researcher never to have met a person with the disease they are working on, with the consequence that patients’ hopes and aspirations or the burden of the illness are not appreciated (Garden et al, 2016).…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…On top of this, there is evidence of concern among publics regarding enhancing human capabilities. A 2016 Pew Center Survey (Funk, Kennedy and Podrebarac Sciupac, 2016 [108]) of 4726 people found that Americans expect continued scientific and technological innovation, broadly speaking, to bring helpful change to society. Regarding the use of emerging technologies for brain enhancement, 68% of Americans were not supportive, with only 32% supportive.…”
Section: Enhancementmentioning
confidence: 99%